ANALISIS KARAKTER SISWA PADA KEGIATAN EKSTRAKURIKULER PRAMUKA SISWA KELAS V DI SD NEGERI 1 AIR GEGAS - Depita Kirana; Adi Saputra; Rifki Hanif Setiawan (STKIP Subang, 2026)
Early habituation is an important step in building character education and school culture through the implementation of values within the school environment. In the current era, students’ character values tend to decline. Although scouting activities at the school are conducted regularly every Thursday, students’ character development has not been formed optimally, thus requiring an in-depth analysis of the characters emerging through these activities. This study aims to describe the religious, creative, disciplined, honest, and responsible character traits of fifth-grade students during scouting activities. This research employed a qualitative descriptive method using data collection techniques including observation, interviews, and documentation. Data sources consisted of the scouting instructor, the fifth-grade homeroom teacher, and 20 fifth-grade students participating in scouting activities. Data analysis involved data reduction, data presentation, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results indicate that scouting activities at SD Negeri 1 Air Gegas have successfully fostered students’ character through hands-on practices conducted every Thursday, such as habituation of prayer, cheer creation, and adherence to rules. The character values developed include religiosity, creativity, honesty, discipline, and responsibility. These activities also contribute to creating an inclusive and supportive school environment while strengthening students’ sense of identity toward their school.